Influence of CYP2D6 phenotype on adherence, adverse effects, and attitudes in aripiprazole and risperidone users - Hietala, Elina; Solismaa, Anssi; Lähteenvuo, Markku; Ahola-Olli, Ari V.; Häkkinen, Katja; Suokas, Kimmo; Isometsä, Erkki; Suvisaari, Jaana; Kieseppä, Tuula; Holm, Minna; Tiihonen, Jari; Lönnqvist, Jouko; et al. (Cambridge University Press (CUP), 2025)
Non-adherence and negative attitudes towards medication are major problems in treating psychotic disorders. Cytochrome P450 2D6 (CYP2D6) contributes to the metabolism of aripiprazole and risperidone, and variations in CYP2D6 activity may affect treatment response or adverse effects. However, the impact of these variations on adherence and medication attitudes is unclear. This study investigates the relationships between CYP2D6 phenotype, self-reported adherence, adverse effects, and attitudes among aripiprazole and risperidone users. The study analysed data from the SUPER-Finland cohort of 10,474 adults with psychotic episodes, including 1,429 aripiprazole and 828 risperidone users. The Attitudes towards Neuroleptic Treatment (ANT) questionnaire assessed adherence and adverse effects in all patients, while medication-related attitudes were examined in a subgroup of 1,000 participants. Associations between CYP2D6 phenotypes and outcomes were analysed using logistic regression and beta regression in aripiprazole and risperidone groups separately. Among risperidone users, we observed no association between CYP2D6 phenotypes and adherence, adverse effects, or attitudes. Similarly, we found no link between adherence and CYP2D6 phenotypes among aripiprazole users. However, aripiprazole users with the ultrarapid CYP2D6 phenotype had more adverse effects (OR = 1.71, 95 % CI 1.03-2.90, p = 0.041). Among aripiprazole users, CYP2D6 ultrarapid phenotype was associated with less favourable attitudes towards antipsychotic treatment (beta = -0.48, p = 0.023). These findings provide preliminary evidence that the ultrarapid CYP2D6 phenotype is associated with increased adverse effects and negative attitudes towards antipsychotic medication among aripiprazole users. CYP2D6 phenotype did not influence adherence, adverse effects, or attitudes among risperidone users.